'Sense and Sensibility' : Medical Pluralism in Postsocialist Croatia - Bukovčan, Tanja (Array, 2007)
In the presentation I will outline my PhD research, the main topic of which was medical pluralism in postsocialist Croatia. The research deals with interrelatedness and co-existence of biomedical and non-biomedical systems in the city of Zagreb, the capital of Croatia. The staring point of my research were the patients, their attitudes towards illness and health and their reasons for the selection of specific therapies, healers and/or medical systems, as well as the factors (cultural, social, generational, educational, religious, political-ideological, financial) which determined their choice. The postsocialist period in Croatia started in the 1990ies and, among other changes, brought about significant changes to the biomedical health care system, which became less state funded and much more market oriented and, as the consequence, more expensive to the end-users, the patients. Simultaneously, and maybe partly because of this, the non-biomedical systems were more ‘ loud’ and more visible, ranging from folk healers, herbalists, through exorcists, bioenergy practitioners to ayurveda or acupuncture. My research findings were the following: for the majority of the people I interviewed biomedicine came first, but in case of chronic, terminal or psychosomatic illnesses, they sought alternative therapies ranging from folk healers to established non-Western medical systems. As an ethnographer, I was faced with moving stories of loss and trauma (stories of war refugees, patients with PTSS, disabled people), as well as stories of miraculous healings and becoming well again (‘ feeling like being born again’ ) which made me re-examine my position of observer, interpreter and analyst. Anthropology’ s unique possibility of understanding and interpreting other cultural norms and relams and its application to this very sensitive field full of emotional attitudes, opinions, beliefs, metaphors and meanings may, in the case of applied medical anthropology, suggest a possible shift towards acitivism.